A Circadian Output Circuit Controls Sleep-Wake Arousal in Drosophila. - Guo, F.; Holla, M.; Díaz, M.M.; Rosbash, M. (Neuron, 2018)
The Drosophila core circadian circuit contains distinct groups of interacting neurons that give rise to diurnal sleep-wake patterns. Previous work showed that a subset of dorsal neurons 1 (DN1s) are sleep-promoting through their inhibition of activity-promoting circadian pacemakers. Here we show that these anterior-projecting DNs (APDNs) also "exit" the circadian circuitry and communicate with the homeostatic sleep center in higher brain regions to regulate sleep and sleep-wake arousal. These APDNs connect to a small, discrete subset of tubercular-bulbar neurons, which are connected in turn to specific sleep-centric ellipsoid body (EB)-ring neurons of the central complex. Remarkably, activation of the APDNs produces sleep-like oscillations in the EB and affects arousal. The data indicate that this APDN-TuBusup-EB circuit temporally regulates sleep-wake arousal in addition to the previously defined role of the TuBu-EB circuit in vision, navigation, and attention.